Impact of Tax Avoidance on Firm Value and Cost of Debt: Evidence from Indonesia - Agus Arianto Toly; Linsey Natadjaja; Gizannda Gandapurnama (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2026)
This research aims to evaluate the impact of tax avoidance on both firm value and cost of debt for firms and diverse businesses. In performing its functions and duties, this paper will apply hypothesis testing methods, starting from a total of two hypotheses. The sample used involves 803 non-financial firms listed on the IDX during the period from 2021 to 2024, which amounts to a total of 3,212 observations. The findings vary across the sectors, which is partially inconsistent with the initial hypotheses that tax avoidance affects firm value and the cost of debt negatively. Regarding its effect on firm value, tax avoidance has a positive impact in the healthcare sector, but a negative impact on the consumer staples and utilities sectors. Meanwhile, for the cost of debt, tax avoidance shows a positive effect in the industrial and material sector, but a negative impact on the real estate and utilities sector. This research contributes to practice by helping companies design their tax avoidance strategies and by providing investors with insights into their investment decisions.